Ensuring Hajj Fund Sustainability: The Interplay Of Investment Portofolios and Macroeconomic Indicators - Nayla Shakila; Wiku Suryomurti (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The management of Hajj funds in Indonesia faces critical challenges in maintaining financial sustainability as rising pilgrimage costs outpace investment yields. Grounded in Modern Portfolio Theory and Arbitrage Pricing Theory, this study aims to analyze the transmission mechanisms linking asset allocation strategies specifically liquid Islamic banking instruments, long-term sukuk, and real-sector direct investments and systemic macroeconomic variables (inflation and the USD/IDR exchange rate) to BPKH's investment returns. Utilizing an Autoregressive Distributed Lag (ARDL) framework, this research analyzes quarterly data from 2018 to 2025. To ensure robustness despite a small finite sample size (N = 32), the structural model is verified using exact finite-sample critical bounds, while a structural break dummy is incorporated to capture the operational disruptions caused by the COVID-19 pandemic. The findings reveal a long-term cointegration relationship with a high speed of adjustment toward equilibrium at 72% per quarter (ECT= -0.72). Placements in Islamic banking and early-lagged sukuk allocations provide stable, positive impacts on fund growth. Conversely, direct investments exhibit a long-term strategic paradox, yielding negative long-run coefficients due to high cross-border operational overhead and maintenance costs. Mechanistically, domestic inflation stands as the most destructive risk factor that directly devalues the real purchasing power of the returns, whereas exchange rate shocks remain transitory and mean-reverting. The novelty of this study lies in its dynamic, break-adjusted modeling that evaluates socio-religious portfolio resilience against global shocks. These findings provide critical policy implications for BPKH to transition toward active inflation-hedging and dual-currency matching strategies to ensure intergenerational equity and future financial independence.